PROBLEMATIKA INDEPENDENSI HAKIM SEBAGAI PELAKSANA KEKUASAAN KEHAKIMAN - Zahra, Adinda Thalia; Sinaga, Aditia; Firdausi, Muhammad Rafli (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The purpose of writing this work is to share thoughts with the general public regarding the issue of the independence of judges as the executors of judicial power. Writing functions as a legal tool for judges to carry out their role in adjudicating and making decisions in a case so that they are not affected by interference or influence from other power groups, both within the internal organs of executive power and within the organs of executive power. Even though religious norms are used as guidelines in this article because it is known that Indonesian people are generally quite obedient to norms, the findings show that judges still make decisions in Indonesia to investigate and find a sense of justice in society